Malaysia-Indonesia relationship must not be limited to diplomatic area alone - Herman - New Sabah Times English, (KK) (New Sabah Times English (KK), 2014)
SINTOK: Relationship between Malaysia and Indonesia must not be limited to diplomatic and bilateral segments alone but rather expanded to other areas said Indonesian Ambassador to Malaysia, Herman Prayitno.